Ethical issues in using a cocaine vaccine to treat and prevent cocaine abuse and dependence. Issue 4 (2nd August 2004) - Hall, W; Carter, L
Abstract : A "cocaine vaccine" is a promising immunotherapeutic approach to treating cocaine dependence which induces the immune system to form antibodies that prevent cocaine from crossing the blood brain barrier to act on receptor sites in the brain. Studies in rats show that cocaine antibodies block cocaine from reaching the brain and prevent the reinstatement of cocaine self administration. A successful phase 1 trial of a human cocaine vaccine has been reported. The most promising application of a cocaine vaccine is to prevent relapse to dependence in abstinent users who voluntarily enter treatment. Any use of a vaccine to treat cocaine addicts under legal coercion raises major ethical issues. If this is done at all, it should be carefully trialled first, and only after considerable clinical experience has been obtained in using the vaccine to treat voluntary patients. There will need to be an informed community debate about what role, if any, a cocaine vaccine may have as a way of preventing cocaine addiction in children and adolescents.